Non-marine Ostracoda (Crustacea) collected from pet shops and a hobbyist’s aquaria in Japan, including two new species - Smith, Robin James; Ozawa, Hirokazu; Nishida, Sumiko; Nakai, Shizuko (Zootaxa, 2024)
Samples obtained from pet shops and a hobbyist’s aquaria in Japan have revealed a diverse non-marine ostracod fauna, consisting of 19 species, all contaminants of aquaria stocked with exotic fish, shrimps and/or aquatic plants. Of these, six are newly recorded for Japan, including two new species, belonging to the genera Pseudostrandesia and Tanycypris. Pseudostrandesia tenebrarum Smith & Ozawa, 2021, previously suspected to be an alien species in Japan, was again found in pet shops in this study. We also report living specimens of Potamocypris acuminata Fuhrmann & Goth, 2011, a species previously only known from Pleistocene deposits of Germany. The six new records for Japan reported herein are likely alien species as evidenced by previous records or congeneric species, with origins in East Asia, South East Asia, and the Americas. Thus, there are now seven ostracod species recognized as probable alien hitchhikers in the Japanese pet trade. This study highlights that the pet trade is a viable route for hitchhiking ostracod species to enter Japan, and such species have the potential to become invasive.